Accelerating tooth movement during orthodontic therapy by using device-assisted therapy: Akselerasi pergerakan gigi selama perawatan ortodontik dengan bantuan perangkat terapi - Karima Qurnia Mansjur; Rasdiana Rasyid (Makassar Dental Journal, 2021)
Background: In the present era there is precipitously increase in demand for orthodontic treatment especially among adult pa-tients. Fixed orthodontic treatment usually lasts up to 2-3 years, so it has some disadvantages like a higher predisposition to caries, gingival recession, and root resorption. This increases the demand to find the best method to increase tooth movement with the least possible disadvantages. Objective: to explore the successful approaches in tooth movemet by using device-assist-ed therapy. Methods: Through literature research. Result: The present information have exposed prosperous development in accelerating orthodontic tooth movement by using device-assisted therapy, includes are vibrational forces, low-level laser the-rapy (LLLT), and low-intensity pulsed ultrasound (LIPUS). Conclusion: LLLT and LIPUS have shown positive outcome, but further investigation should be done for the best energy and duration to achieve the highest success rate.